Effect Of Donor Blood Storage Period on Hemoglobin Levels and Erythrocyte Cell Morphology - Wulandari, Eka Wahyu Putri; Afriansyah, Muhammad Ardi; Sukeksi, Andri (Politeknik Kesehatan Kemenkes Mamuju, 2024)
Blood is a body fluid whose stability can be influenced by both internal and external factors such as storage period. Storing blood specimens for a long time can cause changes in the physiological condition of blood cells such as color, size, shape and cell formation. This study aims to determine the effect of the storage period for donor blood specimens at UTD RSUP dr. Kariadi Semarang on hemoglobin levels and erythrocyte morphology. The research design is an experiment using a modified Time Series design with a pre and posttest control group design. The samples in this study were CPDA-1 (Citrate Phosphate Dextrose Adenine) donor blood specimens at the Blood Transfusion Unit of RSUP dr. Kariadi Semarang. Observation of erythrocyte cell morphology using blood smear preparations (SHD). Primary data was taken from the results of measurements of hemoglobin levels and observations of erythrocyte cell morphology with blood specimens examined directly (day 0) and storage days 1, 2, and 3. Analysis of research data used the One-way Anova statistical test. The results of the One-Way Anova test showed that there was a significant difference in hemoglobin levels on the 3rd day of donor blood storage (p-value 0.000). The results of the evaluation of erythrocyte cell morphology showed that there were abnormalities in crenation morphology on the 3rd day of storage. Blood specimens should be processed immediately after they leave the body because the condition of the blood cells is still stable and optimal for use in laboratory tests.